Knowledge and practices of Internet among teachers: a case study of Tikapur Municipality - Chaudhary, Nathu Ram (Journal of Tikapur Multiple Campus, 2015)
This study was conducted to explore teachers' skills, perceptions, and practices about the use of computer and internet technology in campus of Tikapur Municipality. Questionnaires were distributed to 52 teachers in different departments of TMC and BMC with response rate of 100%. The validity of the questionnaire was approved by a panel of experts at campus. Descriptive statistics and correlation were used to analyze the data. Of the 52 teachers, 96.2% were males and 3.8% were females. Majority of the respondents were between the ages 30-40 years. Further, teachers' perceptions in terms of using computer and internet technology were found to be positive. Finally, the study revealed inverse correlations among internet use, age, and teaching experience. The descriptive results indicated that teachers' knowledge in basic ICT applications as well as integrating computer and internet technology into teaching and learning processes was confounded to web search for information, communication and file handling. These results provide evidence that the introduction of computer and internet technology in teaching and learning has not brought any major changes in the delivery of education in campus of Tikapur Municipality. This also implies that teachers have not shifted from teacher-centered instruction to student-centered learning. From the findings of the study, it is recommended that courses such as computer-supported learning, internet and designing instructional materials should be introduced in initial teacher training programs to improve teachers' level of confidence and perceptions towards the use of ICT.